MODEL TATA KELOLA KOLABORATIF DEWAN KEBIJAKAN PANGAN UNTUK PENGEMBANGAN SISTEM PANGAN LOKAL: TINJAUAN LITERATUR SISTEMATIS - Fauzan Hidayat; Sandi Nurgadi (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2026)
Local food systems face increasingly complex challenges, including food security, sustainability, social equity, and stakeholder coordination. In this context, Food Policy Councils (FPCs) have emerged as collaborative governance mechanisms that bring together governments, civil society organizations, academics, farmers, and private-sector actors in the formulation and implementation of food policies. This study aims to examine the role of Food Policy Councils as collaborative governance mechanisms in local food system development through a Systematic Literature Review (SLR) approach. The study follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and utilizes articles indexed in the Scopus database published between 2015 and 2026. Out of 115 identified records, 30 articles were selected and analyzed based on predefined inclusion and exclusion criteria. The findings indicate that Food Policy Councils represent the most dominant collaborative governance model in local food system development. Key success factors include stakeholder participation, leadership, trust, institutional support, representation, and network partnerships. Major challenges include coordination problems, funding limitations, power imbalances, and resource constraints. The review further reveals that Food Policy Councils contribute to improving food security, food democracy, sustainable food systems, social equity, and community resilience. Based on the synthesis of the reviewed literature, this study proposes an Integrated Food Policy Council Governance Framework that explains the relationship between collaborative governance factors and local food system development outcomes.